Comportement saisonnier du betail zebu en Adamaoua Camerounais. II. La croissance avant sevrage pour les veaux de race locale et les metis demi-sang Brahma - Lhoste, Philippe (1968)
Studies the seasonal response of zebu cattle in Adamawa. Growth of calves before weaning were evaluated on two genetically distinct herds: 248 males and 229 females Metis Brahma, 110 males and 105 females Fulani breed. The birth weight, the monthly weights up to the 8 months age and the daily average again of weight during this period of 244 days were taken in account. The breed, the sex, the season of birth and the chronological order of calving of each were analysed. The following conclusions were drawn: The Metis Brahma had a better speed of growth; the male calves had faster growth than the females; the chronological order of calving had a significant influence on the calf from birth to 3 months age; and the season of birth had an important influence on the performance at the weaning time, thus cattle owner had to obtain the maximum of calvings at the outset of the rainy season.